1974
DOI: 10.1111/j.1365-2621.1974.tb02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Proximate Composition and Mineral Element Content of Three Cultivars of Raw and Roasted Peanuts

Abstract: Yield of kernels, proximate composition (moisture, crude fiber, fat, protein and ash), and content of nine mineral elements–Ca, Mg, P, Na, K, Fe, Cu, Zn and Mn‐are reported for three cultivars of peanuts, raw and roasted. Roasting resulted in higher concentrations of all nutrients measured in the peanuts except moisture and sodium, whose contents decreased. Although statistically significant differences in nutrient content were noted among cultivars, these differences were of little practical importance. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
19
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 7 publications
9
19
1
Order By: Relevance
“…Significant differences were found among the 26 germplasm lines for each of the 11 elements derived fkom peanut seed (Table 2). These results corroborate earlier findings of nutrient differences among cultivars (2,3,4,7,8,10).…”
Section: Methodssupporting
confidence: 83%
“…Significant differences were found among the 26 germplasm lines for each of the 11 elements derived fkom peanut seed (Table 2). These results corroborate earlier findings of nutrient differences among cultivars (2,3,4,7,8,10).…”
Section: Methodssupporting
confidence: 83%
“…The intact peanut kernels contained proteins levels ranging from 20.7 to 29.7% (relative to total weight) with a mean protein content for all samples of 25.2 ± 2.7% (Table 1), which is in line with known average values of protein content in peanut (Oerise et al, 1974). The differences we see in protein content between the samples can be explained by both genetic and environmental factors, in particular the variety cultured and climate and weather conditions (Cobb and Johnson, 1973).…”
Section: Protein Content Of Peanut Kernels and Aqueous Extractssupporting
confidence: 55%
“…Peanut (Arachis hypogaea L) is a seed crop legume that is widely used for human food purposes because of its high nutrition value (Oerise et al, 1974) and sensory attributes. The overall annual production of peanut (including Runner, Virginia, Spanish, and Valencia) in the U.S. in 2014 was 2.4 million tons (Anonymous, USDA NASS report, 2015) harvested from 1.4 million acres.…”
Section: Introductionmentioning
confidence: 99%
“…Derise et al (16) also reported a very similar ash content for Virginia-type peanuts. The mineral composition of peanut seeds is given in Table 2.…”
Section: Resultsmentioning
confidence: 68%